Kriminalisasi Perempuan Pekerja Seks Komersial dalam Perluasan Pasal Zina RUU KUHP - Leony Sondang Suryani; Ani Purwanti (Sawwa: Jurnal Studi Gender, 2018)
This article discusses the Criminal Code Bill which has unjust legal potential because the provision of adultery has been extended to sexual acts by unmarried couples. This article presents an analysis of the possible implications of the Criminal Code Bill - specifically the section on the adultery of sex workers through the socio-legal method in which a combination of normative legal approaches and social research methods is applied. This article states that broadly defined provisions of adultery can lead to unfair penalties -due to injustice- sex workers who by law must be treated as victims of sexual exploitation and fraud rather than perpetrators of crime.